Public policymaking in Hong Kong : civic engagement and state-society relations in a semi-democracy - Lee, Eliza W. Y., 1962- (Comparative development and policy in Asia series ;, 2013)
"This book discusses civic engagement and public policymaking in postcolonial Hong Kong. Utilizing case studies of citizens' advisory committees involving four policy areas - urban planning, social welfare policy, environmental protection, and arts and culture policy - it examines the interaction between the state and civil society, and explores how far the state opens up its policy process for citizens' participation"--